Respuesta :

Answer:

[tex]a_{n+1}[/tex] = [tex]a_{n}[/tex] + 3

Step-by-step explanation:

the coordinates of the points are

(1, - 6 ), (2, - 3 ), (3, 0 ), (4, 3 ), (5, 6 )

consider the values of y

- 6, - 3, 0, 3, 6

there is a common difference between consecutive terms, that is

- 3 - (- 6) = 0 - (- 3) = 3 - 0 = 6 - 3 = 3

this indicates the sequence is arithmetic with recursive rule

[tex]a_{n+1}[/tex] = [tex]a_{n}[/tex] + d ( d is the common difference )

here d = 3 , then recursive formula is

[tex]a_{n+1}[/tex] = [tex]a_{n}[/tex] + 3 ; with a₁ = - 6

ACCESS MORE